The influence of physical activity on mental health: a systematic review - de Lacerda, Dhiego Alves; do Vale, Maria Eduarda Mulato; de Oliveira, Anaylle Vieira Lacerda; Celeste, Heitor Estrela; Cruz, Kayck Ryan Fernandes; Miranda, José Leonardo Frutuoso; Cavalcante, Ayla Alves; Neto, Valentim Fragoso de Freitas; Braga, Thárcio Ruston Oliveira; Lira, Michely De Sousa; Cezar , Renata Silva (Revista Sistemática, 2024)
This study aims to analyze the relationship between regular physical activity and mental health. A systematic review of the literature was conducted, using electronic databases, such as PubMed and Scopus, to identify relevant studies published in the last 10 years. The results indicate a significant association between physical activity and reduced risk of mental disorders such as anxiety and depression. It is concluded that the promotion of physical activity can play an important role in the prevention and treatment of mental health problems.